PEMBELAJARAN AKSARA MELAYU DI SEKOLAH DASAR - Mahyuni, Sri; Indriani, Indriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The purpose of this development research is to produce Malay Arabic written teaching materials for students majoring in Madrasah Ibtidaiyah Teacher Education with appropriate and effective content, presentation, language and graphics for learning. This study uses an ethography research model where ethnography research is a study of group culture through interviews and observations. Until now, Arabic teaching materials that have developed and are widely used in Indonesia in general are teaching materials used in madrasas and MIN/SD. If the teaching materials are the result of development, the amount is not so much. As long as the demands for innovation and development of Arabic teaching materials continue to roll, nowadays, in line with the dynamics of the development of science and technology. In addition, the demand for Arabic teaching materials that use Indonesian as the language is growing among the majority of introductory students, especially those with a general education background. Thus, one of the needs that teachers must have in carrying out their duties is to develop teaching materials. The development of a teacher's teaching materials is important so that learning is more effective, efficient and does not deviate from the competencies achieved. Keywords: Teaching Materials, Writing Arabic MalayAbstrakTujuan dari penelitian pengembangan ini adalah untuk menghasilkan bahan ajar tulis Arab Melayu bagi siswa jurusan Pendidikan Guru Madrasah Ibtidaiyah dengan isi, penyajian, bahasa dan grafik yang sesuai dan efektif untuk pembelajaran. Penelitian ini menggunakan model penelitian etografi dimana penelitian etnografi merupakan studi tentang budaya kelompok melalui wawancara dan observasi. Sampai saat ini bahan ajar bahasa Arab yang berkembang dan banyak digunakan di Indonesia pada umumnya adalah bahan ajar yang digunakan di madrasah dan MIN/SD. Jika bahan ajar merupakan hasil pengembangan, jumlahnya tidak begitu banyak. Selama tuntutan inovasi dan pengembangan bahan ajar bahasa Arab terus bergulir, dewasa ini sejalan dengan dinamika perkembangan ilmu pengetahuan dan teknologi. Selain itu, Kebutuhan akan bahan ajar bahasa Arab yang menggunakan bahasa Indonesia sebagai bahasa pengantar semakin meningkat di kalangan sebagian besar siswa pengantar, terutama mereka yang berlatar belakang pendidikan umum. Dengan demikian, salah satu kebutuhan yang harus dimiliki guru dalam menjalankan tugasnya adalah mengembangkan bahan ajar. Pengembangan bahan ajar seorang guru penting dilakukan agar pembelajaran lebih efektif, efisien dan tidak menyimpang dari kompetensi yang dicapai.